(untitled) (Metallurgy and Foundry Engineering, 2007)
Possibilities of SigmaScan Pro computer program applications in quantitative characterization of materials microstructure are described in this paper. The studies were carried out for microstructures of different types, i.e. granular single phase, dispersed and lamellar. Furthermore possibilities of shape factors utilization in quantitative studies of microstructure, particularly in range of microstructure sta-bility are presented in details.